2014
DOI: 10.1007/s12253-014-9865-8
|View full text |Cite
|
Sign up to set email alerts
|

The Value of HPV-HR DNA Testing During the Follow-Up After Treatment of CIN3/AIS

Abstract: There is still debate on what is the optimal follow-up protocol after a treatment for preinvasive cervical disease. We performed this study in order to improve diagnostic accuracy of the follow-up protocol and at the same time reducing the number of overtreated patients. One hundred and fourteen patients were followed up after conization for CIN3 and/or AIS at 3-6 month, 9-12 month and 18-24 month intervals, then yearly. The follow-up consisted of cytology, colposcopy with biopsy if needed and HPV testing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Sixteen primary studies [9,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and 4 systematic reviews [47][48][49][50] were included for the role of surgical margins, including one systematic review (summarizing 14 primary works) focusing on the stratified analyses by HPV status that was considered particularly relevant by the panel. Thirteen papers were included for women's age [9,32,33,37,40,42,45,[51][52][53][54][55][56], five for the underlying cytology [34,41,45,55,57] four for viral load [34,45,54,58], seven for grade of CIN [8,9,33,36,37,57,…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen primary studies [9,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and 4 systematic reviews [47][48][49][50] were included for the role of surgical margins, including one systematic review (summarizing 14 primary works) focusing on the stratified analyses by HPV status that was considered particularly relevant by the panel. Thirteen papers were included for women's age [9,32,33,37,40,42,45,[51][52][53][54][55][56], five for the underlying cytology [34,41,45,55,57] four for viral load [34,45,54,58], seven for grade of CIN [8,9,33,36,37,57,…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…For the question comparing 6 with 12 month interval between intervention and the first follow up episode, 22 studies were included [8,9,24,25,34,36,43,44,46,51,[63][64][65][66][67][68][70][71][72][73][74][75], including 7497 women who received their first control at 6 months and 1285 at 12 months. Out of the 18 studies useful for this outcome, only 5 invasive cancers were found, all in the 6 month group (Table 3).…”
Section: Timing Of First Follow Up Episode (Recommendation N 4)mentioning
confidence: 99%
See 1 more Smart Citation